Ferret model to mimic the sequential exposure of humans to historical H3N2 influenza viruses. Issue 2 (9th January 2023) - Chiba, Shiho; Hatta, Masato; Pattinson, David; Yasuhara, Atsuhiro; Neumann, Gabriele; Kawaoka, Yoshihiro
Abstract: Mutations accumulate in influenza A virus proteins, especially in the main epitopes on the virus surface glycoprotein hemagglutinin (HA). For influenza A(H3N2) viruses, in particular, the antigenicity of their HA has altered since their emergence in 1968, requiring changes of vaccine strains every few years. Most adults have been exposed to several antigenically divergent H3N2 viruses through infection and/or vaccination, and those exposures affect the immune responses of those individuals. However, animal models reflecting this 'immune history' in humans are lacking and naïve animals are generally used for vaccination and virus challenge studies. Here, we describe a ferret model to mimic the serial exposure of humans to antigenically different historical H3HA proteins. In this model, ferrets were sequentially immunized with adjuvanted recombinant H3HA proteins from two or three different H3HA antigenic clusters in chronological order, and serum neutralizing antibody titers were examined against the homologous virus and viruses from different antigenic clusters. For ferrets immunized with a single HA antigen, serum neutralizing antibody titers were elevated specifically against the homologous virus. However, after immunization with the second or third antigenically distinct HA antigen in chronological order, the ferrets showed an increase in more broadly cross-reactive neutralizing titers against the antigenically distinct viruses and against the homologous virus. Sequentially immunized animals challenged with an antigenically advanced H3N2 virus showed attenuated virus growth and less body temperature increase compared with naïve animals. These results suggest that sequential exposure to antigenically different HAs elicits broader neutralizing activity in sera and enhances immune responses against more antigenically distinct viruses Our findings may partly explain why adults who have been exposed to antigenically divergent HAs are less likely to be infected with influenza virus and have severe symptoms than children.